2010
DOI: 10.1074/jbc.m109.043786
|View full text |Cite
|
Sign up to set email alerts
|

Fat-specific Protein 27 Undergoes Ubiquitin-dependent Degradation Regulated by Triacylglycerol Synthesis and Lipid Droplet Formation

Abstract: The fat-specific protein 27 (Fsp27), a protein localized to lipid droplets (LDs), plays an important role in controlling lipid storage and mitochondrial activity in adipocytes. Fsp27-null mice display increased energy expenditure and are resistant to high fat diet-induced obesity and diabetes. However, little is known about how the Fsp27 protein is regulated. Here, we show that Fsp27 stability is controlled by the ubiquitin-dependent proteasomal degradation pathway in adipocytes. The ubiquitination of Fsp27 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 31 publications
8
51
0
Order By: Relevance
“…It is ubiquitinated and degraded via the proteasome, as are CIDEA and other lipid droplet proteins such as adipocyte triglyceride lipase (ATGL) ( 26,27 ). These results are consistent with those in a paper published during preparation of the manuscript ( 28 ). We also report that TNF-␣ , interleukin-1 ␤ (IL-1 ␤ ), or IFN-␥ treatment of mouse adipocytes causes rapid FSP27 depletion followed by decreased lipid droplet size and enhanced lipolysis.…”
supporting
confidence: 79%
“…It is ubiquitinated and degraded via the proteasome, as are CIDEA and other lipid droplet proteins such as adipocyte triglyceride lipase (ATGL) ( 26,27 ). These results are consistent with those in a paper published during preparation of the manuscript ( 28 ). We also report that TNF-␣ , interleukin-1 ␤ (IL-1 ␤ ), or IFN-␥ treatment of mouse adipocytes causes rapid FSP27 depletion followed by decreased lipid droplet size and enhanced lipolysis.…”
supporting
confidence: 79%
“…Here, we demonstrate that Cideb is also detected in the Golgi apparatus, an important site for VLDL lipidation and maturation. Cideb has been previously shown to localize to the LDs and ER by fl uorescent staining and biochemical fractionation, similar to Cidea and Fsp27 ( 43,44,47,52,53 ). Here, using a sucrose density gradient centrifugation approach, we observed that Cideb is also localized to the Golgi apparatus.…”
Section: Discussionmentioning
confidence: 48%
“…Depletion of SREBP-1 had no effect on CIDEC mRNA expression in the presence or absence of insulin (data not shown), suggesting that SREBP-1 is not involved in the regulation of CIDEC expression. It has been shown that CIDEC stabilization is associated with triacylglycerol synthesis and LD formation ( 55 ). The present study suggested that SREBP-1c mediates insulin/JNK2-induced de novo fatty acid synthesis.…”
Section: Discussionmentioning
confidence: 58%